S-Tel: An Avatar Based Sign Language Telecommunication System - Kuroda, Tomohiro; Sato, Kosuke; Chihara, Kunihiro (International Journal of Virtual Reality, 1998)
Although modern telecommunication has drastically our daily lives, the audibly challenged cannot benefit from such telecommunication because it is based on phonetic media. This paper introduces a new telecommunication system for sign language utilizing VR technology, which enables natural sign conversation on the conventional analogue telephone line. In this method, a person converses with his/her partys avatar instead of the party's live video. As a speaker's actions are transmitted as kinematic data, the transmitted data is ideally compressed without losing both the language and non-language information of spoken signs. A prototype system, S-TEL, which implements this method on UDP/IP, proved the effectiveness of avatar-based communication for sign conversation via a real lossy channel.